Development and implementation of an educational programme to enhance health literacy on prescribed medication instruction among diabetes mellitus patients on treatment at Ga-Dikgale Village Clinics in Capricorn District, Limpopo Province - Ngoatle, Charity (My University, 2021)
Health literacy related to medication use or instructions is crucial to diabetes mellitus patients. The verbal or written instructions are given to diabetes mellitus patients regarding medication use is important to improve patient care, safety, and compliance to treatment. However, the information provided to diabetes mellitus patients regarding medication use is not known as they continue to experience complications. The study aimed to develop and implement an educational programme, to enhance health literacy on prescribed medication instructions among diabetes mellitus patients on treatment at Ga-Dikgale village clinics in Capricorn District, Limpopo Province. The objectives of the study were to explore the knowledge, and practices of diabetes mellitus patients on treatment. Thus, to describe the provided information regarding prescribed medication usage contained in the diabetes mellitus medication packaging, medicine leaflets, and prescriptions. Therefore, to also describe the effects of poor health literacy on prescribed medication instructions among diabetes mellitus patients on treatment at Ga- Dikgale village clinics in Capricorn District, Limpopo Province. Data were collected using a mixed-method approach and a mixed-method sampling technique was used to select 18 participants for the qualitative strand. Whereas, there were 137 respondents for the quantitative strand. Tesch’s proposed eight steps to analyse the data were adopted to analyse the qualitative data and SSPS version 25 was used for analysing quantitative data. The results showed the following findings: patients lack knowledge about diabetes as a disease, misinterpret medication instructions, and are noncompliant to the treatment. This non-compliance is intensified by negligence and poor comprehension of medication instructions. As a result, to help diabetes mellitus patients with compliance with diabetes treatment, ongoing implementation of the educational programme should be instituted. The Limpopo’s Department of Health has to offer in-service vii education to the health professionals, who dispense medications on the interpretation of medication instructions. The high school curriculum is ought to incorporate health literacy to prescribe medication instructions.
Thesis (Ph.D.(Nursing Science)) -- University of Limpopo, 2021
Keywords: Educational programme; Health literacy; Prescribed medication; Instructions; Diabetes mellitus Patients; Treatment; Health literacy; Diabetes -- Oral therapy; Oral medication; Diabetics; Diabetes -- Treatment -- South Africa -- Limpopo